The Balance protocol: a pragmatic weight gain prevention randomized controlled trial for medically vulnerable patients within primary care - Miriam B. Berger; Dori M. Steinberg; Sandy Askew; John A. Gallis; Cayla C. Treadway; Joseph R. Egger; Melissa C. Kay; Bryan C. Batch; Eric A. Finkelstein; Abigail DeVries; Ashley Brewer; Gary G. Bennett (BMC Public Health, 2019)
Abstract Background For patients with obesity who are not ready for or experience barriers to weight loss, clinical practice guidelines recommend provider counseling on preventing further weight gain as a first-line treatment approach. Unfortunately, evidence-based weight gain prevention interventions are not routinely available within primary care. To address this gap, we will implement a pragmatic 12-month randomized controlled trial of a digital weight gain prevention intervention delivered to patients receiving primary care within a network of Federally Qualified Community Health Centers in central North Carolina. Methods Balance (Equilibrio in Spanish) is a pragmatic effectiveness trial that will randomize adult patients who have overweight or obesity (BMI of 25–40 kg/m2) to either: 1) a weight gain prevention intervention with tailored behavior change goals and tracking, daily weighing on a network-connected electronic scale, and responsive weight and goal coaching delivered remotely by health center registered dietitians; or 2) a usual care program with automated healthy living text messages and print materials and routine primary care. The primary outcome will be weight gain prevention at 24-months, defined as ≤3% change in baseline weight. To align with its pragmatic design, trial outcome data will be pulled from the electronic health record of the community health center network. Discussion For underserved, often rurally-located patients with obesity, digital approaches to promote a healthy lifestyle can curb further weight gain. Yet enrolling medically vulnerable patients into a weight gain prevention trial, many of whom are from racial/ethnic minorities, can be difficult. Despite these potential challenges, we plan to recruit a large, diverse sample from rural areas, and will implement a remotely-delivered weight gain prevention intervention to medically vulnerable patients. Upcoming trial results will demonstrate the effectiveness of this pragmatic approach to implement and evaluate a digital weight gain prevention intervention within primary care. Trials registration NCT03003403. Registered December 28, 2016.